Influence of filler-binder ratio and temperature on the Linear Viscoelastic (LVE) characteristics of asphalt mastics - Chaudhary M.; Saboo N.; Gupta A.; Steineder M.; Hofko B. (My University, 2025)
This study describes an investigation into the Linear Viscoelastic (LVE) limit/range of asphalt mastics prepared with different fillers. Effect of temperature and Filler-Binder (F/B) ratio on the LVE limits of mastics has been studied. The interrelation between Linear Viscoelastic Complex Modulus (G∗LVE)and corresponding LVE limit has been examined. To compare the denouement of the study, the SHRP LVE strain criteria is also included which quantifies the applicability of the criteria to asphalt mastics. The lower LVE limit at high F/B ratio is the antithesis of the LVE limit at higher temperatures. The change in coefficient of determination (R2) was prominent with change in F/B ratio whereas temperature shows a marginal shift in R2 value indicating the dominance of F/B in the LVE range. The LVE limits obtained from the study were relatively conservative compared to those from SHRP study showing the unsuitability of applying SHRP criteria directly to mastics. © 2021 Taylor & Francis Group, London.